Legal Interpreting in Canada's Eastern Arctic - Akeeshoo, Atsainak (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThis paper outlines the historical development of the Canadian legal system in the Eastern Arctic since the turn of the century, particularly after the Second World War. It discusses the challenges and difficulties faced by legal interpreters in situations where fundamental concepts of Indo-European justice were initially foreign to the Inuit. It explores some of the problems created by the differences between the lexicon and syntax of Inuktitut and English. It describes how the already difficult task of legal interpreting has been compounded by the recent change in the Jury Act of the NWT, in September, 1989, allowing unilingual jurors to sit on juries and how this situation has been handled.